Association of Serum 25-Hydroxyvitamin D Concentration with Pulmonary Function in Young Adults - Craveiro, V (2018)
The role of vitamin D on pulmonary function is unclear and is mostly studied in patients, smokers and elderly people. The aim of this paper was to evaluate the association between serum 25-hydroxyvitamin D [25(OH)D] concentration and pulmonary function in young adults. Cross-sectional analysis of 499 individuals that were evaluated at 21 years of age as part of the population-based cohort Epidemiological Health Investigation of Teenagers in Porto (EPITeen). Serum 25(OH)D was categorized according to the Institute of Medicine. Pulmonary function was evaluated using spirometry. Linear regression models were used to estimate the regression coefficients (beta) and its 95% confidence intervals (95% CI), and were adjusted for confounders. Education, smoking, body mass index, and season of evaluation were determinants of serum 25(OH)D concentration. Prevalence of serum 25(OH)D concentration < 50 nmol/L was 48.9%. A decrease in all pulmonary function parameters, with the decrease of serum 25(OH)D, was observed. The higher effect was found for peak expiratory flow (PEF). Having as reference participants with serum 25(OH)D concentration >= 50 nmol/L, PEF was significantly lower for those with a concentration of 30 to < 50 nmol/L (beta = -0.576; 95% CI: -0.943, -0.210), and for those with a concentration of <30 nmol/L (beta = - 0.650; 95% CI: -1.155, -0.146). Although only PEF attained statistical significance, the consistent results with the other parameters support the role of serum 25(OH)D to promote better pulmonary function in young adults.